2011
DOI: 10.1002/jbm.a.33123
|View full text |Cite
|
Sign up to set email alerts
|

Structural surface changes and inflammatory responses against alginate‐based microcapsules after exposure to human peritoneal fluid

Abstract: Microencapsulation of cells is a promising approach to prevent rejection in the absence of immunosuppression. Clinical application, however, is hampered by insufficient insight in factors influencing biocompatibility of the capsules in humans. In the present study we exposed alginate-based capsules prepared of different types of alginate to human peritoneal fluid. Subsequently we studied the physicochemical changes of the capsule's surface by applying micro-Fourier Transform Infrared Spectroscopy. We did test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…As we implanted capsules with identical physico-chemical and mechanical properties we questioned whether the capsules might undergo changes in vivo that might be hold responsible for the differences in responses. As we found in a recent in vitro study [46] that the properties of the capsules surface may change after exposure to human peritoneal fluid we questioned whether there might be a difference in properties of the intermediate and high G capsules after implantation. To this end we implanted in a separate series of experiments capsules in the peritoneal cavity of rats which were retrieved by peritoneal lavage at 1, 3, and 7 days after implantation.…”
Section: Surface Properties After Implantationmentioning
confidence: 93%
See 3 more Smart Citations
“…As we implanted capsules with identical physico-chemical and mechanical properties we questioned whether the capsules might undergo changes in vivo that might be hold responsible for the differences in responses. As we found in a recent in vitro study [46] that the properties of the capsules surface may change after exposure to human peritoneal fluid we questioned whether there might be a difference in properties of the intermediate and high G capsules after implantation. To this end we implanted in a separate series of experiments capsules in the peritoneal cavity of rats which were retrieved by peritoneal lavage at 1, 3, and 7 days after implantation.…”
Section: Surface Properties After Implantationmentioning
confidence: 93%
“…Upon exposure to body fluids microcapsules will adsorb bioactive components which will change the properties of the capsule surface and the responses against the capsules Table 3 Elemental surface composition of alginate-PLL capsules (n ¼ 4). [16,46]. In recent in vitro studies we showed that fluctuations in pH in body fluids changes the properties and charge density of capsules making capsules more susceptible for adsorption of body proteins and inflammatory responses [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complement and coagulation proteins are present at other sites than in blood, such as in the peritoneal fluid 107,108 .…”
Section: Relevance To the In Vivo Situationmentioning
confidence: 99%